Effect of Cow Urine and IBA on the Growth of Sweet Leaf (Sauropus androgynus (L.) Merr.) Cuttings - Fawziyah Nurshabrina; arifah rahayu; oktavianus lt (Universitas Djuanda Bogor, 2019)
Sweet leaf (Sauropus androgynus (L.) Merr.), a leaf vegetable that is generally propagated vegetatively with cuttings. This study aims to determine the effect of accession and administration of natural and synthetic auxin growth regulators on the growth of sweet leaf cuttings. This study uses factorial Randomized Complete Design consisting of two factors, namely accession (Banten from Pandeglang, Bogor from Tajur, and Cianjur from Cugenang) and auksin combination (IBA 100%R, urine 25%R + IBA 75%R, urine 50%R + IBA 50%R, urine 75%R + IBA 25%R, and urine 100%R). The results showed that the growth of Cianjur accession had the best results on the percentage of growth cuttings, the percentage of shoot buds, shoot height, number of shoots, number of leaves, percentage of rooted cuttings, and number of roots compared to Banten and Bogor accessions. Giving urine 100%R significantly increases plant height, shoot height, number of shoots, and number of sweet leaf plant roots compared with other auxin combinations. The combination treatment of auxin and accession showed results that were not significantly different from the variable root length and weight of the harvest. In sweet leaf plants, cow urine can replace the use of IBA (Indole Butyric Acid). Keywords: Sauropus androgynus, vegetative, urine, IBA